BADATANCY TOYS COMPETITION STRATEGY USES AN INTERNAL-EXTERNAL MATRIX, CPM, SWOT, SPACE, AND GRAND STRATEGY - Saputri, Adiya Agustin Eka Saputri; Rahayu, Agus; Dirgantari, Puspo Dewi (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2022)
This study aims to identify the internal and external environment of Badatancy Toys and determine a good business strategy for Badatancy Toys in order to compete in the market. The research method used in this study is a qualitative descriptive method. Power collection techniques using interviews and observation both directly and indirectly. The data obtained were analyzed using the IFE, EFE, CPM, TOWS, SPACE, and Grand Strategy matrices. From the research results, it is known that the results of the IFE Matrix are 2.74 and the EFE Matrix is ​​2.56. The final results of the analysis of the CPM Matrix, TOWS, SPACE Grand Strategy show that alternatives that can be applied to the Badatancy Toys business are increasing product promotion, maintaining customer service, expanding market share, developing products, and penetrating the market.